A method for preparing a copper-cuprous oxide-copper bismuthate ternary composite

The copper-cuprous oxide-copper bismuthate ternary complex was prepared by a synergistic "one-pot" method involving heterogeneous interface and homogeneous redox reaction, which solved the problems of complex preparation steps and difficulty in quantitative control, and realized the preparation of highly efficient photocatalytic materials.

CN120420990BActive Publication Date: 2025-10-28BENGBU COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510628160.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-10-28
Estimated Expiration
2045-05-15

AI Technical Summary

Technical Problem

In the prior art, the preparation steps of the copper-cuprous oxide-copper bismuthate ternary complex are complicated and difficult to quantitatively control.

Method used

A synergistic "one-pot" method combining heterogeneous in-situ redox reaction and homogeneous redox reaction was adopted to generate a copper-cuprous oxide-copper bismuthate ternary complex by reacting sodium bismuthate dihydrate, copper sulfate, and sodium sulfite under hydrothermal conditions.

Benefits of technology

A copper-cuprous oxide-copper bismuthate ternary complex with a simple preparation process and easy quantitative control was achieved, forming an atomic or molecular-level heterostructure, which improved the photocatalytic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120420990B_ABST
    Figure CN120420990B_ABST
Patent Text Reader

Abstract

This invention relates to the field of photocatalysis technology and provides a method for preparing a copper-cuprous oxide-copper bismuthate ternary complex. Sodium bismuthate dihydrate, copper sulfate, and sodium sulfite are added to a hydrothermal reactor containing distilled water to obtain a solid-liquid mixture. Under hydrothermal conditions, the solid-liquid mixture undergoes a synergistic reaction between sodium bismuthate and sodium sulfite solutions in a heterogeneous interface in-situ redox reaction and between copper sulfate and sodium sulfite solutions in a homogeneous redox reaction to generate the copper-cuprous oxide-copper bismuthate ternary complex. The advantages of this invention are: a one-pot method for preparing elemental copper-cuprous oxide-copper bismuthate ternary complex through a synergistic combination of heterogeneous interface in-situ redox reaction and homogeneous redox reaction; and the preparation steps are simple, convenient, and easily quantitatively controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalysis technology, and in particular to a method for preparing a copper-cuprous oxide-copper bismuthate ternary composite. Background Technology

[0002] Since its development, semiconductor photocatalysis technology has achieved fruitful results and developed rapidly in the field of environmental governance and pollutant purification. It has been widely studied and applied in air purification, wastewater treatment, and water splitting for hydrogen production. However, the effective implementation of this technology depends on a stable and efficient photocatalyst.

[0003] Cuprous oxide (Cu2O), as a narrow bandgap semiconductor material, can fully absorb visible light energy, making it an ideal visible-light photocatalyst with great application potential in fields such as solar energy utilization. However, the easy recombination of photogenerated electrons and holes limits the development and utilization of single semiconductor photocatalysts. Therefore, cuprous oxide can be modified by composite processing to combine it with other semiconductors, generating heterostructures that facilitate the separation of photogenerated carriers. By preparing composite photocatalysts, the photocatalytic efficiency can be improved.

[0004] Copper bismuthate, as a semiconductor material, possesses excellent photocatalytic performance, and existing research has confirmed its superior photocatalytic properties. Therefore, effectively combining Cu₂O and CuBi₂O₄ holds promise for obtaining a composite photocatalytic material with stable performance and higher light utilization efficiency. Furthermore, the surface plasmon resonance (SPR) effect of elemental copper can significantly enhance the absorption of visible light by the photocatalyst, thereby improving its photocatalytic activity. Therefore, effectively combining elemental copper, cuprous oxide, and copper bismuthate to obtain a ternary composite material of elemental copper-cuprous oxide-copper bismuthate can effectively separate photogenerated carriers and fully utilize visible light energy, thus achieving high photocatalytic efficiency.

[0005] However, in the existing technology, ternary composite materials are usually prepared by stepwise synthesis, which has the problems of complex preparation steps and difficulty in quantitative control.

[0006] Therefore, it is necessary to propose a simple and easily quantitatively controllable method for preparing copper-cuprous oxide-copper bismuthate ternary composites to address the above problems. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide a method for preparing a copper-cuprous oxide-copper bismuthate ternary complex. The method is to prepare the elemental copper-cuprous oxide-copper bismuthate ternary complex by a synergistic "one-pot" method of in-situ redox reaction at the heterogeneous interface and homogeneous redox reaction. The preparation steps are simple, the operation is convenient, and the quantitative control is easy.

[0008] The present invention solves the above-mentioned technical problems by adopting the following technical solutions:

[0009] A method for preparing a copper-cuprous oxide-copper bismuthate ternary complex involves adding sodium bismuthate dihydrate (NaBiO3·2H2O), copper sulfate (CuSO4), and sodium sulfite (Na2SO3) to a hydrothermal reactor containing distilled water to obtain a solid-liquid mixture. Under hydrothermal conditions, the solid-liquid mixture undergoes a synergistic reaction between sodium bismuthate and sodium sulfite solutions in a heterogeneous interfacial redox reaction and between copper sulfate and sodium sulfite solutions in a homogeneous redox reaction to generate the copper-cuprous oxide-copper bismuthate ternary complex (Cu-Cu2O-CuBi2O4). The reaction process is as follows:

[0010]

[0011] As one of the preferred embodiments of the present invention, the molar ratio of sodium bismuthate dihydrate, copper sulfate, and sodium sulfite is 2:2:(2+x), 0.5 <x<1。

[0012] As one of the preferred embodiments of the present invention, the solid-liquid mixture is reacted under hydrothermal conditions at 180-200°C for 10-30 hours.

[0013] As one of the preferred embodiments of the present invention, after the hydrothermal reaction, the process further includes the steps of "centrifugation of the reaction product, washing with distilled water, and vacuum drying" to finally obtain a copper-cuprous oxide-copper bismuthate ternary nanocomposite.

[0014] As one of the preferred embodiments of the present invention, the vacuum drying conditions are: 60°C, 0.1 MPa vacuum, vacuum drying for 2 hours.

[0015] As one of the preferred embodiments of the present invention, in the final copper-cuprous oxide-copper bismuthate ternary nanocomposite product, the average grain size of copper bismuthate is 93.5-125.1 nm, and the average grain size of cuprous oxide is 15.3-19.7 nm.

[0016] Reaction principle:

[0017] Sodium bismuthate dihydrate is a sparingly soluble solid. Through a heterogeneous interface redox reaction, its pentavalent bismuth is reduced to trivalent bismuth by sulfite ions. In the presence of copper ions, sodium bismuthate dihydrate is converted to copper bismuthate. In this reaction, sodium bismuthate dihydrate acts as a sacrificial template, forming copper bismuthate on the template surface. Simultaneously, when sodium bismuthate dihydrate is reduced to trivalent bismuth by sulfite ions, hydroxide ions are also generated, providing an alkaline environment. Under alkaline conditions, divalent copper ions are reduced to monovalent copper ions by sodium sulfite, generating cuprous oxide, which is also deposited on the surface of the sodium bismuthate dihydrate solid template. Furthermore, excess sodium sulfite further reduces some of the cuprous oxide to elemental copper, achieving a one-pot synthesis of the elemental copper-cuprous oxide-copper bismuthate ternary complex.

[0018] The advantages of this invention compared to the prior art are:

[0019] (1) In the preparation process of the composite of the present invention, sodium bismuthate dihydrate acts as a sacrificial template to generate copper bismuthate on the surface of the template; at the same time, when sodium bismuthate dihydrate is reduced to trivalent bismuth by sulfite ions, hydroxide ions are also generated to provide an alkaline environment; in the alkaline environment, divalent copper ions are reduced to monovalent copper ions by sodium sulfite to generate cuprous oxide, and the generated cuprous oxide is also deposited on the surface of the solid template of sodium bismuthate dihydrate; and excess sodium sulfite further reduces some of the cuprous oxide to elemental copper; based on this, the present invention realizes the one-pot synthesis of elemental copper-cuprous oxide-copper bismuthate ternary composite, the preparation steps are simple and the operation is convenient, and at the same time, elemental copper, cuprous oxide and copper bismuthate can effectively form atomic or molecular heterostructures, with good composite effect;

[0020] (2) The preparation process of the composite of the present invention is easy to control quantitatively and reduces the aggregation of product particles (in-situ conversion deposition on solid surface can inhibit the migration of product particles and reduce aggregation), and is easy to industrialize. Attached Figure Description

[0021] Figure 1 The image shows a transmission electron microscope image of the product of Example 2 of the present invention (the scale bar in the image is 100 nm).

[0022] Figure 2 The XRD patterns of the products of various embodiments of the present invention are shown (with reference to the XRD patterns of elemental copper, cuprous oxide and copper bismuthate). Detailed Implementation

[0023] The embodiments of the present invention are described in detail below. These embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments. Furthermore, the reagents and experimental methods used in the following embodiments and experimental examples, unless otherwise specified, are all conventional reagents or methods in the art and will not be described again.

[0024] Example 1

[0025] This embodiment describes a method for preparing a copper-cuprous oxide-copper bismuthate ternary composite:

[0026] Weigh out 0.01 mol sodium bismuthate dihydrate (NaBiO3·2H2O), 0.01 mol copper sulfate (CuSO4), and 0.013 mol sodium sulfite (Na2SO3) in a molar ratio of 2:2:2.6, and add them to a 50 ml hydrothermal reactor containing 40 ml distilled water. Stir until homogeneous to obtain a solid-liquid mixture.

[0027] The solid-liquid mixture was reacted under hydrothermal conditions at 180℃ for 10 hours. Through the synergistic effect of the in-situ redox reaction at the heterogeneous interface between sodium bismuthate and sodium sulfite solution and the homogeneous redox reaction between copper sulfate solution and sodium sulfite solution, a copper-cuprous oxide-copper bismuthate ternary complex (Cu-Cu₂O-CuBi₂O₄) was generated. The reaction process is as follows:

[0028]

[0029] The reaction product was centrifuged, washed with distilled water, and vacuum dried at 60°C and 0.1 MPa for 2 h to obtain a copper-cuprous oxide-copper bismuthate ternary nanocomposite.

[0030] Example 2

[0031] The preparation method of the copper-cuprous oxide-copper bismuthate ternary composite in this embodiment is basically the same as that in Example 1, except that the solid-liquid mixture is reacted under hydrothermal conditions at 190°C for 10 hours.

[0032] Example 3

[0033] The preparation method of the copper-cuprous oxide-copper bismuthate ternary composite in this embodiment is basically the same as that in Example 1, except that the solid-liquid mixture is reacted under hydrothermal conditions at 190°C for 20 hours.

[0034] Example 4

[0035] The preparation method of the copper-cuprous oxide-copper bismuthate ternary composite in this embodiment is basically the same as that in Example 1, except that the solid-liquid mixture is reacted under hydrothermal conditions at 190°C for 30 hours.

[0036] Example 5

[0037] The preparation method of the copper-cuprous oxide-copper bismuthate ternary composite in this embodiment is basically the same as that in Example 1, except that the solid-liquid mixture is reacted under hydrothermal conditions at 200°C for 10 hours.

[0038] Example 6

[0039] This embodiment describes a method for preparing a copper-cuprous oxide-copper bismuthate ternary composite:

[0040] Weigh out 0.01 mol sodium bismuthate dihydrate (NaBiO3·2H2O), 0.01 mol copper sulfate (CuSO4), and 0.014 mol sodium sulfite (Na2SO3) in a molar ratio of 2:2:2.8, and add them to a 50 ml hydrothermal reactor containing 40 ml distilled water. Stir until homogeneous to obtain a solid-liquid mixture.

[0041] The solid-liquid mixture was reacted under hydrothermal conditions at 190℃ for 10 hours. Through the synergistic effect of the in-situ redox reaction at the heterogeneous interface between sodium bismuthate and sodium sulfite solution and the homogeneous redox reaction between copper sulfate solution and sodium sulfite solution, a copper-cuprous oxide-copper bismuthate ternary complex (Cu-Cu₂O-CuBi₂O₄) was generated. The reaction process is as follows:

[0042]

[0043] The reaction product was centrifuged, washed with distilled water, and vacuum dried at 60°C and 0.1 MPa for 2 h to obtain a copper-cuprous oxide-copper bismuthate ternary nanocomposite.

[0044] Experimental Example 1

[0045] The product obtained in the above examples (taking Example 2 as an example) was observed under a transmission electron microscope (TEM), and the results are as follows: Figure 1 As shown.

[0046] from Figure 1 It can be seen that the surface of the large particles (copper bismuthate) is loaded with small particles (cuprous oxide, elemental copper), which initially indicates that the Cu-Cu2O-CuBi2O4 composite of the present invention is successful.

[0047] Experiment Example 2

[0048] X-ray diffraction (XRD) analysis was performed on the products obtained in the above embodiments, and the results are as follows: Figure 2 As shown.

[0049] Figure 2 The XRD patterns of the products prepared in various embodiments of the present invention are shown below, with elemental copper (PDF#04-001-3621), cuprous oxide (PDF#04-002-0905), and copper bismuthate (PDF#04-006-6769) as references. Figure 2 It can be seen that in the XRD patterns of the products of the various embodiments of the present invention, only the characteristic diffraction peaks of copper bismuthate, cuprous oxide and elemental copper are present, and there are no diffraction peaks of other phases, which further indicates that the product is a ternary nanocomposite of elemental copper-cuprous oxide-copper bismuthate.

[0050] Meanwhile, based on the XRD analysis of the products of the above embodiments, the average grain size of copper bismuthate and cuprous oxide in each embodiment was calculated using the Scherrer formula, as shown in Table 1.

[0051] Table 1. Average grain size of copper bismuthate and cuprous oxide in the products of each embodiment.

[0052]

[0053]

[0054] Statistical analysis was performed on the above results:

[0055] (1) When sodium bismuthate dihydrate, copper sulfate and sodium sulfite were added to distilled water in a molar ratio of 2:2:2.6 and hydrothermally reacted at 190°C for 10 h, 20 h and 30 h respectively (as shown in Examples 2, 3 and 4), the average grain sizes of copper bismuthate in the resulting products were 106.5 nm, 108.7 nm and 113.3 nm, respectively, and the average grain sizes of cuprous oxide were 17.1 nm, 17.9 nm and 18.3 nm, respectively; indicating that the average grain sizes of copper bismuthate and cuprous oxide increased slightly with the extension of hydrothermal reaction time.

[0056] (2) When sodium bismuthate dihydrate, copper sulfate and sodium sulfite were added to distilled water in a molar ratio of 2:2:2.6 and hydrothermal reactions were carried out at 180℃, 190℃ and 200℃ for 10 h (as shown in Examples 1, 2 and 5), the average grain sizes of copper bismuthate in the products were 93.5 nm, 106.5 nm and 125.1 nm, respectively, and the average grain sizes of cuprous oxide were 15.3 nm, 17.1 nm and 19.7 nm, respectively; indicating that the average grain sizes of copper bismuthate and cuprous oxide increased with the increase of hydrothermal reaction temperature.

[0057] Therefore, in the preparation process of this invention, the average grain size of the components in the product can be controlled by appropriately controlling the hydrothermal reaction temperature and reaction time.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a copper-cuprous oxide-copper bismuthate ternary composite, characterized in that, Sodium bismuthate dihydrate, copper sulfate, and sodium sulfite were added to a hydrothermal reactor containing distilled water to obtain a solid-liquid mixture. The molar ratio of sodium bismuthate dihydrate, copper sulfate, and sodium sulfite was 2:2:(2+x), where 0.5 < x < 1. The solid-liquid mixture was reacted under hydrothermal conditions at 180~200℃ for 10~30h. Through the synergistic effect of the in-situ redox reaction at the heterogeneous interface between sodium bismuthate and sodium sulfite solution and the homogeneous redox reaction between copper sulfate and sodium sulfite solution, a copper-cuprous oxide-copper bismuthate ternary complex was generated. The reaction process is as follows: 。 2. The method for preparing the copper-cuprous oxide-copper bismuthate ternary composite according to claim 1, characterized in that, Following the hydrothermal reaction, the process also includes centrifugation of the reaction products, washing with distilled water, and vacuum drying to finally obtain a copper-cuprous oxide-copper bismuthate ternary nanocomposite.

3. The method for preparing the copper-cuprous oxide-copper bismuthate ternary composite according to claim 2, characterized in that, The vacuum drying conditions are: 60℃, 0.1Mpa vacuum degree, vacuum drying for 2 hours.

4. The method for preparing the copper-cuprous oxide-copper bismuthate ternary composite according to claim 2, characterized in that, The final copper-cuprous oxide-copper bismuthate ternary nanocomposite product has an average grain size of 93.5~125.1 nm for copper bismuthate and an average grain size of 15.3~19.7 nm for cuprous oxide.

Citation Information

Patent Citations

  • Double-Z-type CuO / CuBi2O4 / Bi2O3 composite photocatalyst as well as preparation method and application thereof

    CN113731430A

  • Method for preparing copper and bismuth co-doped bamboo charcoal catalyst through citric acid complexation and application of copper and bismuth co-doped bamboo charcoal catalyst

    CN119386885A